RESULTS OF AN OPEN CLINICAL STUDY OF THE EFFICACY OF LEFLUNOMIDE IN RHEUMATOID ARTHRITIS - I M Marusenko (Современная ревматология, 2009)
Objective: To evaluate the efficacy of leflunomide versus methotrexate in patients with rheumatoid arthritis. Subjects and methods. The study included 24 patients receiving leflunomide who underwent the determination of changes in the articular syndrome: the Ritchie index, the number of tender and swollen joints, pain, and the total activity of the disease, by using the visual analogue scale, morning stiffness in minutes. Therapeutic efficiency was evaluated by the EULAR criteria on the basis of changes in the Disease Activity Score (DAS) 4 and by using the criteria for a response to therapy ACR 20/ACR 50/ACR 70. Results. A rapid development of a clinical effect was noted in the use of leflunomide: the parameters of the articular syndrome improved at 3-month follow-up. According to the EULAR criteria, just after 1-month leflunomide treatment; good and satisfactory effects were achieved in 12,5 and 28% of the patients, respectively; and according to the ACR, there was a 50% improvement in 51% of the patients and 20% improvement in 22%. The patients treated with leflunomide showed a significantly reduced increment in the number of new erosions whereas those who took methotrexate caused only a reduction in the rate of increment. Conclusion. The new basic drug leflunomide is as effective as the gold standard methotrexate, at the same time it allows clinical improvement to be more rapidly achieved. Leflunomide also slows down the rate of progression of erosive arthritis and it is well tolerated.